Pengenalan dan Pencegahan Penyakit Paru Obstruktif Kronis (PPOK) pada Tingkat Remaja di MTSN 1 Medan - Huwaina Af’idah; Ade Risma; Juhri Panjaitan; Nazli Ba’iah; Feby Ayu; Yasmin Novithaharah Suprianto (Sevaka : Hasil Kegiatan Layanan Masyarakat, 2024)
Chronic Obstructive Pulmonary Disease (COPD) is a chronic disease that is a global health problem, including among teenagers. The increase in COPD cases in teenagers is also influenced by changes in modern lifestyle, such as exposure to cigarette smoke, air pollution and other unhealthy habits. Insufficient knowledge about the risks of smoking and exposure to air pollutants as well as a lack of awareness of the importance of maintaining lung health have led to an increase in the incidence of this disease at a young age. The aim of this research is to increase teenagers’ understanding of Chronic Obstructive Pulmonary Disease and its prevention, so that they can understand and be able to carry it out in their daily activities. This research method uses a quantitative design using pre-test and post-test questionnaires. Providing pre-test and post-test questionnaires, according to the number of participants who took part in the outreach on the Introduction and Prevention of COPD. This research was conducted in April 2024 at MTsN 1 Medan with 31 respondents. The results of this socialization showed that there was an increase in the knowledge of MTsN 1 Medan students by >80.65% after being given presentation material by the PKM team. The conclusions and suggestions given are to improve health education, healthy lifestyles, early detection, and appropriate intervention to prevent the development of chronic obstructive pulmonary disease (COPD) in adolescents.